Possible role of QRS duration in the right ventricle as a perioperative monitoring parameter for right ventricular function: a prospective cohort analysis in robotic mitral valve surgery - Watanabe, Ryota; Hori, Kotaro; Ishihara, Keisuke; Tsujikawa, Shogo; Hino, Hideki; Matsuura, Tadashi; Takahashi, Yosuke; Shibata, Toshihiko; Mori, Takashi (Frontiers in Cardiovascular Medicine, 2024)
The clinical importance of the right ventricle (RV) has recently been recognized; however, assessing its function during cardiac surgery remains challenging owing to its complex anatomy. A temporary transvenous pacing catheter is a useful tool in the small surgical field of minimally invasive cardiac surgery, and an electrocardiogram recorded through the catheter is composed of the direct electrophysiological activity of the RV. Therefore, we hypothesized that QRS duration in the RV (QRSRV) could be a useful monitoring parameter for perioperative RV function.We conducted a prospective cohort analysis involving adult patients undergoing robotic mitral valve repair. A bipolar pacing catheter was inserted using X-ray fluoroscopy, and the QRSRV duration was assessed at four time points: preoperative baseline, during one-lung ventilation, after weaning from cardiopulmonary bypass, and before the end of surgery. At the same time points, right ventricular fractional area change (RVFAC) measured by transesophageal echocardiography and QRS duration at V5 lead of the body surface electrocardiogram (QRSV5) were also evaluated.In the 94 patients analyzed, QRSRV duration was significantly prolonged during robotic mitral valve repair (p=0.0009), whereas no significant intraoperative changes in RVFAC were observed (p=0.2). By contrast, QRSV5 duration was significantly shortened during surgery (p<0.00001). Multilinear regression showed a significant correlation of QRSRV duration with RVFAC (p=0.00006), but not with central venous pressure (p=0.9), or left ventricular ejection fraction (p=0.3). When patients were divided into two groups by postoperative QRSRV>100 or ≤100 ms, 25 patients (26.6%) exhibited the prolonged QRSRV duration, and the mean increase in the postoperative QRSRV from preoperative baseline was 12 ms (p=0.001), which was only 0.6 ms in patients with QRSRV≤100 ms (p=0.6). Cox regression analysis showed that prolonged postoperative QRSRV duration was the only significant parameter associated with a longer ICU stay after surgery (p=0.02; hazard ratio, 0.55).Our data suggest that QRSRV duration is a useful parameter for monitoring the RV during cardiac surgery, possibly better than a commonly used echocardiographic parameter, RVFAC. An electrophysiological assessment by QRSRV duration could be a practical tool for the complex anatomy of the RV, especially with limited modalities in perioperative settings.